THE EFFECT OF ACCOUNTING PROFIT AND LEVERAGE ON STOCK RETURNS WITH FIRM SIZE AS A MODERATING VARIABLE - Sari, Cindy Ersella (ABDI EQUATOR, 2024)
Stock returns are an essential thing for investors because it is the profit received by investors for their investments. This research aims to determine the effect of accounting profits and leverage on stock returns with firm size as a moderating variable in food and beverage subsector companies listed on the Indonesia Stock Exchange in the 2017-2022 period. The independent variables used in this study include accounting profit and leverage. The dependent variable in this study is stock returns, while firm size is used as a moderating variable. This study uses quantitative associative. The research sample was determined using purposive sampling to obtain 45 companies. The analysis technique used is multiple linear regression analysis and moderated regression analysis (MRA). The results show that partially accounting profit has a positive effect on stock returns. But, the Debt to Equity Ratio negatively affects stock returns. Meanwhile, firm size can moderate by strengthening the influence of accounting profits on stock returns. In contrast, firm size does not moderate the influence of the Debt to Equity Ratio on stock returns. Meanwhile, the accounting profit and Debt to Equity Ratio can simultaneously influence stock returns.